Supramalleolar osteotomies: what and when? - Paulo César de César (Journal of the Foot & Ankle)
Supramalleolar osteotomy is an option in treating ankle osteoarthritis, being the main indication in cases with partial joint involvement and preserving at least 50% of the joint surface. With an adequate understanding of the pathology and a proper surgical indication for joint realignment, most patients do not need conversion to arthrodesis or ankle arthroplasty with short or medium follow-up. Level of evidence V; Expert opinion.